GE_GERICHTE C/23532/2016 vom 6. Februar 2018 - GE Cour de justice (2018)
ACTION EN LIBÉRATION DE DETTE ; REPRISE DE DETTE PRIVATIVE ; COMPENSATION DE CRÉANCES | CPC.317.al2; CPC.177; CO.120.al1; CO.176.al1; CO.175.al1